Exploration of factors that influence sustainable consumption behavior (empirical study of skin care clean beauty consumers in Semarang city) - Andi Tri Haryono; Sinta Petri Lestari (Jurnal Info Sains : Informatika dan Sains, 2024)
This research aims to explore the extent and manner in which factors influence sustainable consumer behaviour, focusing on consumers using clean-beauty skincare products in the city of Semarang, Indonesia. The purpose of this study is to identify and examine the influence of social media influencers (SMI), environmental knowledge (EK), environmental influences (EI), promotion of sustainable consumption (PSC), and sustainable consumption behaviour intention (SCBI) on sustainable consumption behaviour (SCB). The sample for this survey consists of 198 respondents, specifically teenage girls in the city of Semarang, Indonesia. The sampling method for this research is random sampling, and data were collected through an online survey using Google Forms. The research approach utilized is a quantitative descriptive design, and data analysis employed the Structural Equation Model-Partial Least Square (SEM-PLS) method.Overall, the research findings consistently support the initial hypotheses. The results indicate that factors such as Social Media Influencers (SMIs), EnvironmentalKnowledge (EK), Promotion of Sustainable Consumption (PSC), and Sustainable Consumption Intention (SCI) significantly influence Sustainable Consumption Behaviour (SCB). This study recommends that clean-beauty skincare companies consistently utilize social media for marketing purposes to provide ecological consciousness education, sustainably promote their products, and enhance consumer engagement, particularly in the context of environmental sustainability issues.